An asymptomatic Lima dissection after a programmed hybrid revascularization procedure turned to nightmare. Issue 5 (3rd September 2022) - Marinakis, Sotirios; Lalmand, Jacques; Cappeliez, Serge; De Bruyne, Yasmine; Viste, Claire; Aminian, Adel; Dolatabadi, Dariouch; El Nakadi, Badih
Abstract: A 71-year-old female with symptomatic bitroncular coronary ischemic disease was admitted in our hospital for hybrid revascularization. She presented significant stenosis of the proximal and middle left anterior descending artery (LAD) and of the second segment of right coronary artery (RCA). She was scheduled for an Endoscopic Atraumatic Coronary Artery Bypass (EACAB) of the left internal mammary artery (LIMA) to LAD and staged percutaneous coronary intervention (PCI) to RCA after the EACAB. Control of LIMA permeability after RCA PCI showed LIMA dissection with TIMI 2 flow to LAD. Decision to stent a freshly implanted LIMA led to LIMA rupture. An emergent LAD revascularization with a saphenous vein graft and control of bleeding was successfully performed. Patient was discharged at day 10 from the hospital.